2022
DOI: 10.1044/2021_lshss-21-00064
|View full text |Cite
|
Sign up to set email alerts
|

Functional Communication Abilities in Youth With Cerebral Palsy: Association With Impairment Profiles and School-Based Therapy Goals

Abstract: Purpose: The aim of this study was to examine the relationship between functional communication skills, underlying speech, language, and cognitive impairments and school-based speech pathology services in students with cerebral palsy (CP). Method: Thirty-five participants with CP who had Individualized Education Programs (IEPs) were classified according to the Communication Function Classification System (CFCS). Participants completed laboratory assessm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This may fit Vygotsky's proximal development theory, 3 namely that children depend on interaction with their environment for development. Other studies have reported that functional communication is not important for receptive language 33,34 . However, these studies could not adequately assess receptive language in all children because of their motor impairments.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may fit Vygotsky's proximal development theory, 3 namely that children depend on interaction with their environment for development. Other studies have reported that functional communication is not important for receptive language 33,34 . However, these studies could not adequately assess receptive language in all children because of their motor impairments.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have reported that functional communication is not important for receptive language. 33,34 However, these studies could not adequately assess receptive language in all children because of their motor impairments. In the present study, we used uniform assessment tools tailored to each child's operational needs, which may explain differences between our findings and previous research.…”
Section: Discussionmentioning
confidence: 99%
“…College students' self-esteem, linguistic proficiency, and ability to engage in meaningful conversations can all benefit from a strong foundation in interpersonal communication skills. Therefore, applying grammatical competence (linguistic performance) in various communicative contexts is essential to interpersonal communication skills (Daniluk, 2020;Koopmans, 2022;Nath, 2019).…”
Section: Introductionmentioning
confidence: 99%